Evaluation of an Intensive Outpatient Program for Combat Veterans With PTSD. (2nd October 2018) - Cameron, Amy Y.; Capone, Christy; Mamon, Daria
ABSTRACT: There is an identified need within the Veterans Affairs (VA) Healthcare System to provide robust treatment for combat veterans with PTSD. Although empirically supported treatments for PTSD are available within the VA system, the dropout rate is high and many veterans remain symptomatic after treatment has ended, indicating a need for further treatment development. In addition, some veterans require a higher level of care over the course of treatment but a stay at a residential facility is often not feasible. The purpose of this article is to present a newly developed intensive outpatient program, designed to bridge the gap between inpatient and outpatient levels of care, for combat veterans with PTSD. The program provides intensive psychoeducation on PTSD and associated symptoms such as guilt, shame, moral injury and avoidance, skill building to cope with intensive emotions, and in-vivo exposure activities delivered in an intensive group format. Initial results indicate that it may be feasible to implement an intensive outpatient program within existing outpatient resources, and that doing so may help veterans reduce PTSD symptoms, increase social support, and enhance the quality of individual psychotherapy after completion of the program.